THE RELATIONSHIP BETWEEN PARAMETERS FISHING GROUND AGAINTS THE EFFORT OF LARGE PELAGIC FISHERIES IN THE INDIAN OCEAN - Harry Agustian; T. Ersti Yulika Sari; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Sea surface temperature (SST) and chlorophyll-a is an important parameter Oceanography for estimate the abundance and distribution of fish. The purpose of this research is to know the variability of SST and chlorophyll-a spatially and temporally, and to analyze the relationship between SST and chlorophyll-a by catch. The research area is located in the Indian Ocean. The data used is satellite data Aqua MODIS image of level 3 were downloaded via the site ERDDAP and fisheries data used is the large pelagic fish catches landed in PPS Bungus. All variables were analyzed variability. SST data interpretation and chlorophyll-a with the interpretation of the data mapped catches further analyzed using multiple regression analysis. From processing the image data on a monthly basis SST highest average value in May is 30.7 0C while the lowest average in the can in January is 29.4 0C. The values of chlorophyll-a highest average in February and September with a concentration of 0.17 mg/m3, while the lowest average value in April and May in the amount of 0.12 mg/m3. While the density variability CPUE highest average value in August amounted to 72.22 while the lowest density values CPUE in September is 2.73. As for the seasonal average value of the highest SPL season inbetween I of 34.1 0C and the lowest in East season is 32.5 0C. Chlorophyll-a seasonally highest in the transition season II with a value of 0.15 mg/m3 whereas for the other seasons have the same concentration value of 0.13 mg/m3. The relationship between the parameters of the fishing effort is not tight correlation only in November high at 0.61 the influence of X1 and X2 to Y is equal to 37%. Seasonal hubugannya closely not only on the season Southwestern highest correlation with r value of 0.22, while the greatest effect of 5%.Keywords: sea surface temperature (SST), chlorophyll-a, variability, the Indian Ocean, CPUE